N-doped modified MOFs (Metal-Organic Frameworks) derived core-shell nanoreactor as well as preparation method and application thereof

By performing nitrogen doping modification on MOFs materials and surface coating SiO2, and using two-step calcination method to prepare a catalyst with core-shell structure, the problems of low catalytic activity and harsh process conditions of the existing catalyst are solved, and high efficiency is achieved. The stable conversion of furfural to furfurfural alcohol is suitable for industrial applications.

CN119456012APending Publication Date: 2025-02-18HUBEI UNIV OF AUTOMOTIVE TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411660048.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing non-precious metal catalysts used for catalyzing transfer and hydrogenation of α,β-unsaturated aldehydes have low catalytic activity, strict catalytic process conditions, poor cyclic catalytic performance, and difficult to achieve industrial application, especially in terms of furfural conversion and selectivity. There are shortcomings.

Method used

The N-doped modified MOFs material was synthesized by hydrothermal reaction using cobalt salt, organic ligand and nitrogen sources, and N-doped modified MOFs derivatization with core-shell structure was prepared by surface coating SiO2 and two-step calcination. Core-shell nanoreactor.

Benefits of technology

The catalyst exhibits excellent catalytic activity and stability under mild conditions, can efficiently catalyze the conversion of furfural to furfurfurol, with a conversion rate of up to 99%, a selectivity of up to 95%, and has good cycle stability, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456012A_ABST
    Figure CN119456012A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of material preparation and chemical engineering, and particularly relates to an N-doped modified MOFs (Metal-Organic Frameworks) derived core-shell nanoreactor as well as a preparation method and application thereof. The preparation method comprises the following steps: taking cobalt as a node metal, synthesizing an N-doped modified MOFs material with an organic ligand and a nitrogen source through a hydrothermal reaction, then coating the surface of the material with porous silicon dioxide, and preparing the N-doped modified MOFs derived core-shell nanoreactor through a two-step calcination method. The MOFs derived core-shell nanoreactor prepared by the invention has a large specific surface area, a rich pore structure and excellent catalytic activity and stability, and is high in catalytic activity, good in recycling stability and suitable for large-scale popularization and application when being used as a catalyst for alpha, beta-unsaturated aldehyde transfer hydrogenation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material preparation and chemical engineering, and more specifically, to an N-doped modified MOFs-derived core-shell nanoreactor, a preparation method thereof, and an application thereof. Background Art

[0002] With the continuous consumption of fossil energy and the deteriorating ecological environment worldwide, the development of renewable energy has become an urgent and important issue. Converting biomass resources into high-value-added chemicals and using them as a supplement to chemical raw materials can reduce human dependence on traditional petrochemical products, thereby alleviating problems such as fossil resource shortages and petrochemical pollution. Furfural (FAL) is recognized as a key platform chemical that can be produced from lignocellulosic biomass. Hydrogenating furfural to prepare furfuryl alcohol is one of the ways to increase its added value. Its selective hydrogenation product furfuryl alcohol is an extremely important intermediate in the synthesis of fine chemicals, especially in the production of synthetic fibers, lysine, isothermal resins and vitamin C.

[0003] At present, there are three main methods for reducing furfural to furfuryl alcohol: (i) high-pressure hydrogen hydrogenation with copper chromite as an effective catalyst in industry; (ii) high-pressure hydrogen hydrogenation with precious metals (Pd, Rh, Ru and Pt) and non-precious metals (Ni, Cu and Co) as catalysts; (iii) transfer hydrogenation with alcohols as hydrogen source. Among them, the hydrogen source used in the high-pressure hydrogenation with industrial catalysts and precious metals and non-precious metals as catalysts is hydrogen, and most of them are carried out at high temperatures and pressures, with harsh operating conditions and high requirements for reactor and reaction safety. Large-scale use in production not only poses safety risks but also causes resource shortages.

[0004] In recent years, transfer hydrogenation, as a safe and environmentally friendly selective hydrogenation method, has attracted great attention in the preparation of high value-added products from biomass resources. Currently, the research on furfural selective hydrogenation is mainly divided into precious metal catalysts and non-precious metal catalysts.

[0005] Reference (Catalysis Today, 2019, 324: 49-58) loaded Pd on N-doped porous carbon by impregnation method, using 2-butanol as hydrogen source. When the reaction temperature was 120 °C and the reaction time was 10 h, the furfural conversion rate was 92% and the furfuryl alcohol selectivity was 84%. Reference (Applied Catalysis A: General, 2018, 563: 177-184) prepared Ru(CO) / rGO catalyst by impregnation method. Under the optimal conditions, the furfural conversion rate was 93% and the furfuryl alcohol selectivity was as high as 98%. Although precious metal catalysts have good catalytic performance in the selective hydrogenation reaction of furfural, the catalyst itself has high economic value and high cost investment, making it difficult to achieve industrial production.

[0006] The literature (Journal of Catalysis, 2016, 336: 107-115) prepared a Cu / ZnO non-precious metal catalyst by co-precipitation. The study found that the catalytic performance was best when the copper loading was the lowest. After 24 hours, the conversion rate of furfural was only 60%, but the selectivity of furfuryl alcohol was as high as 98%. The literature (Acs Sustainable Chemistry & Engineering, 2017, 5(1):942-947) used Fe 2+ and Fe 3+ The γ-Fe3O4@HAP catalyst was prepared by coprecipitation in an alkaline solution. It took 10 h of reaction at 180 °C for the furfural conversion rate to reach 96.2% and the furfuryl alcohol yield to reach 91.7%. Although the production cost of non-precious metal catalysts is low, there are problems such as low hydrogenation activity, strict requirements for catalytic process conditions, high energy consumption, high production cost, and difficulty in reuse. Therefore, it is of great significance to develop a low-cost, high-efficiency catalytic performance non-precious metal catalyst that can be used for the transfer hydrogenation of α,β-unsaturated aldehydes, especially the transfer hydrogenation of furfural.

[0007] Metal-organic frameworks (MOFs) are a new type of porous material synthesized by coordination self-assembly of divalent or trivalent metal centers and organic ligands. They have a clear crystal structure, adjustable pore topology, ultra-high surface area and excellent designability, and are widely used. However, the fragile coordination bonding between metal nodes and organic ligands in MOFs materials makes the thermal and chemical stability of MOFs materials poor. Summary of the invention

[0008] In view of the defects of the prior art, the purpose of the present application is to provide an N-doped modified MOFs-derived core-shell nanoreactor, its preparation method and application, aiming to solve the problems of low catalytic activity, strict requirements on catalytic process conditions (such as high temperature (180°C and above), high pressure (7~10MPa) or introduction of hydrogen) of existing non-precious metal catalysts used for catalytic transfer hydrogenation of α,β-unsaturated aldehydes, poor cyclic catalytic performance, and unsuitability for industrial application, and is particularly suitable for the preparation of furfuryl alcohol with high conversion rate and high selectivity of furfural.

[0009] To achieve the above objectives, in a first aspect, the present application provides a method for preparing an N-doped modified MOFs-derived core-shell nanoreactor, comprising the following steps: S1, mixing a cobalt salt, an organic ligand, a nitrogen source and a first solvent for hydrothermal treatment, then collecting a precipitate by centrifugation, and obtaining a N-doped modified MOFs material after washing and drying; S2, dispersing the above-mentioned N-doped modified MOFs material in a second solvent to obtain a dispersion, then adjusting the pH of the dispersion, adding a porogen and ethyl orthosilicate, stirring to react, filtering and collecting the solid, washing, and drying to obtain an N-doped modified MOFs precursor with SiO2 coated on the surface; S3. The N-doped modified MOFs precursor with SiO2 coated on the surface is subjected to a first calcination under an inert atmosphere to form a porous structure; and then subjected to a second calcination under an oxygen-containing atmosphere to promote the complete oxidation of the organic ligand and the formation of a cobalt oxide phase, thereby obtaining an N-doped modified MOFs-derived core-shell nanoreactor.

[0010] Preferably, in step S1, the molar ratio of the cobalt salt, the organic ligand and the nitrogen source is (3-5): (3-6): (2-5).

[0011] Preferably, the cobalt salt is one or more of cobalt chloride, cobalt acetate, cobalt nitrate and cobalt nitrate hydrate.

[0012] Preferably, the nitrogen source is one or more of triethylenediamine, urea, melamine and polyaniline.

[0013] Preferably, the organic ligand is terephthalic acid.

[0014] Preferably, the first solvent and the second solvent are each independently methanol, ethanol, N,N -dimethylformamide, N,N - one or more of diethylformamide and dimethyl sulfoxide.

[0015] Preferably, in step S1, the temperature of the hydrothermal treatment is 100°C to 150°C, and the time of the hydrothermal treatment is 24h to 72h.

[0016] Preferably, in step S1, the drying temperature is 50°C to 80°C, and the drying time is 10 h to 15 h.

[0017] Preferably, in step S2, an acid-base regulator is used to adjust the pH of the dispersion to 8-9.

[0018] More preferably, the acid-base regulator is one or more of sodium hydroxide, potassium hydroxide and ammonia water.

[0019] Preferably, in step S2, the mass ratio of the N-doped modified MOFs material to the porogen is 1:(0.1-1); and the concentration of the ethyl orthosilicate in the dispersion is 5%-10%.

[0020] Preferably, the porogen is one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide.

[0021] Preferably, in step S3, the inert atmosphere includes one or more of nitrogen, argon, neon, helium, xenon and krypton.

[0022] Preferably, in step S3, the temperature of the first calcination is 300°C to 350°C, the time is 2 h to 4 h, and the heating rate is 2°C / min to 5°C / min.

[0023] Preferably, in step S3, the oxygen-containing atmosphere includes oxygen and / or air.

[0024] Preferably, in step S3, the temperature of the second calcination is 350°C to 450°C, the time is 2 h to 4 h, and the heating rate is 2°C / min to 5°C / min.

[0025] In a second aspect, the present application provides an N-doped modified MOFs-derived core-shell nanoreactor, which is prepared using the above-mentioned preparation method.

[0026] In the third aspect, the present application provides the use of the above-mentioned N-doped modified MOFs-derived core-shell nanoreactor in catalyzing the transfer hydrogenation reaction of α,β-unsaturated aldehydes, wherein the catalyst used in the transfer hydrogenation reaction of α,β-unsaturated aldehydes is the above-mentioned N-doped modified MOFs-derived core-shell nanoreactor.

[0027] Preferably, the α,β-unsaturated aldehydes include one or more of furfural, 5-hydroxymethylfurfural, acrolein, 2-furanacrolein, cinnamaldehyde, 4-methylcinnamaldehyde, 4-fluorocinnamaldehyde, 4-bromocinnamaldehyde, crotonaldehyde and citral.

[0028] Preferably, the mass ratio of the N-doped modified MOFs-derived core-shell nanoreactor and the α,β-unsaturated aldehyde is (0.025-0.05):(0.8-1).

[0029] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art: (1) This application uses cobalt as a node metal, and synthesizes N-doped MOFs materials through hydrothermal reaction with organic ligands and nitrogen sources, then coats the surface of the material with porous silica, and prepares a N-doped MOFs-derived core-shell nanoreactor with a core-shell structure through a two-step calcination method. The MOFs-derived core-shell nanoreactor not only retains the characteristics of MOFs materials with large specific surface area and rich pore structure, but also improves the stability and defect degree of the material, has excellent catalytic activity and stability, expands the application range of MOFs materials, and provides a new idea for efficient catalytic transfer hydrogenation of α,β-unsaturated aldehydes.

[0030] (2) This application uses MOFs materials as templates to transform them into porous materials that are more stable than the original MOFs, and retains the shape characteristics of the parent MOFs to a large extent, which can provide more active sites for catalytic reactions. Nitrogen doping modification can effectively increase the degree of defects in the material and further enhance the adsorption of α, β-unsaturated aldehydes. At the same time, the introduction of nitrogen can serve as a receiving site for transfer hydrogenation protons, thereby improving the catalytic activity. At the same time, the porous silica coated on the surface can effectively inhibit the agglomeration of MOFs during the calcination process, making it have good dispersibility and effectively improving the stability of the catalyst. The preparation process of the N-doped modified MOFs-derived core-shell nanoreactor provided in this application is simple, the raw materials are low-cost and green, and no precious metal materials are introduced to efficiently catalyze the transfer hydrogenation of α, β-unsaturated aldehydes. The preparation cost is low and the economy is higher.

[0031] (3) The N-doped modified MOFs-derived core-shell nanoreactor provided in the present application is applied to the transfer hydrogenation of α,β-unsaturated aldehydes. It can use solvents as hydrogen donors and exhibit excellent catalytic activity under mild reaction conditions. It can also maintain excellent hydrogenation performance after multiple cycles, and is suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a flow chart for preparing the N-doped modified MOFs-derived core-shell nanoreactor provided in the examples of the present application; Figure 2 This is the SEM image of Co3O4@NC@SiO2 prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0034] In the description of this application, it should be understood that the term "and / or" is a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The symbol " / " herein indicates that the associated objects are in an or relationship, for example, A / B means A or B.

[0035] In the specification and claims of the present application, the terms "first" and "second" etc. are used to distinguish different objects rather than to describe the specific order of the objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.

[0036] In the description of the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0037] In the description of the embodiments of the present application, unless otherwise specified, “plurality” means two or more than two.

[0038] like Figure 1 As shown, the present application provides a method for preparing an N-doped modified MOFs-derived core-shell nanoreactor, comprising the following steps: S1, mixing a cobalt salt, an organic ligand, a nitrogen source and a first solvent for hydrothermal treatment, then collecting a precipitate by centrifugation, and obtaining a N-doped modified MOFs material after washing and drying; S2, dispersing the above-mentioned N-doped modified MOFs material in a second solvent to obtain a dispersion, then adjusting the pH of the dispersion, adding a porogen and ethyl orthosilicate, stirring to react, filtering and collecting the solid, washing, and drying to obtain an N-doped modified MOFs precursor with SiO2 coated on the surface; S3. The N-doped modified MOFs precursor with SiO2 coated on the surface is subjected to a first calcination under an inert atmosphere to form a porous structure; and then subjected to a second calcination under an oxygen-containing atmosphere to promote the complete oxidation of the organic ligand and the formation of a cobalt oxide phase, thereby obtaining an N-doped modified MOFs-derived core-shell nanoreactor.

[0039] In some embodiments, in step S1, the molar ratio of the cobalt salt, the organic ligand and the nitrogen source is (3~5):(3~6):(2~5). By adjusting the molar ratio of the cobalt salt, the organic ligand and the nitrogen source, the contents of Co and N in the N-doped modified MOFs material can be regulated, and the pore structure, specific surface area, morphology and stability of the material can be controlled, thereby improving the catalytic activity of the material.

[0040] In a preferred embodiment, in step S1, the molar ratio of the cobalt salt, the organic ligand and the nitrogen source is (3-4.5):(3-5.5):(2-4.5).

[0041] In some embodiments, the cobalt salt is one or more of cobalt chloride, cobalt acetate, cobalt nitrate and cobalt nitrate hydrate.

[0042] In some embodiments, the organic ligand is terephthalic acid.

[0043] In some embodiments, the nitrogen source is one or more of triethylenediamine, urea, melamine and polyaniline.

[0044] In the present application, the first solvent and the second solvent can ensure that all reactants can be evenly dispersed, which is conducive to the full and uniform progress of the reaction. The present application does not limit the specific types of the first solvent and the second solvent, and solvents with good solubility are preferred. In some embodiments, the first solvent and the second solvent are each independently methanol, ethanol, N,N -dimethylformamide, N,N - one or more of diethylformamide and dimethyl sulfoxide.

[0045] In some embodiments, in order to allow the hydrothermal reaction to proceed more gently and fully, the above-mentioned cobalt salt and organic ligand can be first dispersed in a first solvent to prepare a cobalt salt solution and an organic ligand solution. After the cobalt salt solution and the organic ligand solution are mixed, a nitrogen source is added and stirred until dissolved, and then a hydrothermal treatment is performed.

[0046] In some embodiments, in step S1, the temperature of the hydrothermal treatment is 100°C to 150°C, and the time of the hydrothermal treatment is 24 h to 72 h.

[0047] It is understood that the present application does not limit the above drying method, and a suitable drying method can be selected according to the solvent used and the drying time and temperature can be appropriately adjusted, all within the protection scope of the present application. In some embodiments, the above drying temperature can be 50 ℃ ~ 80 ℃, and the drying time can be 10 h ~ 15 h.

[0048] In some embodiments, in step S2, an acid-base regulator is used to adjust the pH of the dispersion to 8 to 9. The present application does not limit the specific type of the acid-base regulator, and any acid-base regulator reported in the prior art may be used, such as but not limited to sodium hydroxide, potassium hydroxide and ammonia water.

[0049] In some embodiments, in step S2, the mass ratio of the N-doped modified MOFs material to the porogen is 1:(0.1~1), preferably 1:(0.1~0.8); the concentration of the ethyl orthosilicate in the dispersion is 5%~10%, which can achieve precise control of the pore structure of the material, thereby optimizing the adsorption capacity and catalytic activity of the material. The present application forms a core-shell structure by coating the MOFs surface with silicon dioxide, which can provide additional pore space, increase the specific surface area of ​​the material, and improve the chemical and thermal stability of the material.

[0050] In some embodiments, the porogen may be one or more of, but not limited to, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, or octadecyltrimethylammonium bromide.

[0051] In some embodiments, in step S3, the inert atmosphere includes one or more of nitrogen, argon, neon, helium, xenon and krypton.

[0052] In some embodiments, the temperature of the first calcination under an inert atmosphere is 300°C to 350°C, the time is 2 h to 4 h, and the heating rate is 2°C / min to 5°C / min. The present application can stabilize the material structure, improve the thermal stability and chemical stability of the material, and control the pore structure of the material to optimize the adsorption and catalytic performance by calcining the N-doped modified MOFs precursor with SiO2 coated on the surface in a protective atmosphere. When the calcination temperature is too high or the calcination time is too long, it will lead to excessive sintering of the material structure, pore collapse, and reduction of specific surface area, thereby reducing the adsorption and catalytic performance of the material; when the calcination temperature is too low or the calcination time is too short, it is not enough to complete the structural transformation and performance optimization of the material, and a stable pore structure may not be formed, resulting in insufficient thermal stability and chemical stability of the material, affecting its long-term performance and application effect. Furthermore, if the heating rate is too fast, it will cause local overheating of the material and affect the consistency of the structure; if the heating rate is too slow, it will significantly increase energy consumption and production cycle, increase production costs, and reduce economic benefits.

[0053] In some embodiments, in step S3, the oxygen-containing atmosphere includes oxygen and / or air.

[0054] In some embodiments, in step S3, the temperature of the second calcination in an oxygen-containing atmosphere is 350°C to 450°C, the time is 2 h to 4 h, and the heating rate is 2°C / min to 5°C / min, which can promote the complete oxidation of the residual organic ligands in the material, thereby ensuring the formation of the metal oxide phase. When the calcination temperature is too high or the calcination time is too long, it will lead to excessive sintering of the material structure, resulting in agglomeration, a reduction in specific surface area, and thus reduce the adsorption and catalytic properties of the material; when the calcination temperature is too low or the calcination time is too short, the material is insufficient to complete the structural transformation and performance optimization of the material. In addition, a too fast heating rate may cause uneven heating, resulting in local overheating of the material, affecting the consistency of the structure. A too slow heating rate will increase energy consumption and production cycle, increase production costs, and reduce economic benefits.

[0055] The present application uses a two-step calcination method to perform high-temperature pyrolysis on the N-doped modified MOFs precursor with SiO2 coated on the surface, which can convert it into a porous material that is more stable than the original MOFs, significantly improve the degree of defect of the material, and retain the characteristics of the MOFs material such as large specific surface area and rich pore structure. The prepared N-doped modified MOFs-derived core-shell nanoreactor has a stable structure, excellent catalytic performance and good cyclic stability, which effectively improves the conversion rate of α, β-unsaturated aldehydes and expands the application range of MOFs.

[0056] Based on this, the present application provides an N-doped modified MOFs-derived core-shell nanoreactor prepared by the above-mentioned preparation method, namely Co3O4@NC@SiO2.

[0057] The Co3O4@NC@SiO2 provided in the present application can be used as a catalyst for catalyzing the transfer hydrogenation reaction of α,β-unsaturated aldehydes. Based on this, the present application also provides the application of the above-mentioned N-doped modified MOFs-derived core-shell nanoreactor in catalyzing the transfer hydrogenation reaction of α,β-unsaturated aldehydes, wherein the catalyst used in the transfer hydrogenation reaction of α,β-unsaturated aldehydes is the above-mentioned N-doped modified MOFs-derived core-shell nanoreactor.

[0058] In some embodiments, the N-doped modified MOFs-derived core-shell nanoreactor is used in the transfer hydrogenation reaction of α,β-unsaturated aldehydes, comprising the following steps: The N-doped modified MOFs-derived core-shell nanoreactor, α,β-unsaturated aldehyde and reaction solvent are placed in a reactor, an inert gas is introduced to replace the air in the reactor, and then nitrogen is introduced, and the temperature is increased to carry out a transfer hydrogenation reaction.

[0059] In some embodiments, the α,β-unsaturated aldehydes include one or more of furfural, 5-hydroxymethylfurfural, acrolein, 2-furanacrolein, cinnamaldehyde, 4-methylcinnamaldehyde, 4-fluorocinnamaldehyde, 4-bromocinnamaldehyde, crotonaldehyde and citral.

[0060] In some embodiments, the mass ratio of the N-doped modified MOFs-derived core-shell nanoreactor and the α,β-unsaturated aldehyde is (0.025-0.05):(0.8-1).

[0061] In the present application, the reaction solvent can provide a reaction environment suitable for transfer hydrogenation, and also participate in the transfer hydrogenation reaction as a hydrogen donor. The reaction solvent can be, but is not limited to, an alcohol solvent, an alkane solvent, or a formic acid solvent. In some embodiments, the reaction solvent can be isopropanol, cyclohexanol, propanol, or methanol.

[0062] In some embodiments, the nitrogen atmosphere pressure is 0.5 MPa~2.0 MPa, the reaction temperature is 80°C~120°C, and the reaction time is 4 h~20 h.

[0063] In some embodiments, the above application also includes recovering the above N-doped modified MOFs-derived core-shell nanoreactor and then recycling it.

[0064] In some embodiments, the above-mentioned recycling and reuse includes the following steps: centrifuging the reaction liquid after transfer hydrogenation to collect the precipitate, and after washing and drying, recovering the N-doped modified MOFs-derived core-shell nanoreactor.

[0065] In some embodiments, the present application also provides the use of the above-mentioned N-doped modified MOFs-derived core-shell nanoreactor (Co3O4@NC@SiO2 catalyst) as a catalyst in the transfer hydrogenation of furfural to prepare furfuryl alcohol.

[0066] In some embodiments, when the furfural transfer hydrogenation is used to prepare furfural alcohol, the nitrogen atmosphere pressure is 0.5 MPa to 2.0 MPa, the reaction temperature is 80°C to 120°C, the reaction time is 4 h to 20 h, the conversion rate of furfural is as high as 99%, and the selectivity of furfural alcohol is as high as 95%, and furfural alcohol can be prepared with high conversion rate and high selectivity under mild conditions. When the above catalyst is cyclically applied to catalyze the transfer hydrogenation of furfural to prepare furfural alcohol, it has excellent cycle stability, can be reused, and is suitable for industrial induced production applications.

[0067] It should be understood that materials of the same or similar type, model, quality, nature or function as the reagents and instruments used in the following examples can be used to implement the present application. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples can be obtained from commercial sources unless otherwise specified.

[0068] The following are examples: Example 1 1) Preparation of Co-MOF@N@SiO2 materials by solvothermal method Dissolve 4.5 mmol of cobalt salt Co(NO3)2·6H2O and 4.5 mmol of terephthalic acid in 45 mL of N,N -dimethylformamide (DMF) solvent, ultrasonically dispersed for 30 min to obtain a cobalt salt solution (cobalt nitrate solution) and an organic ligand solution (terephthalic acid solution). The organic ligand solution was added to the cobalt salt solution, and then 3 mmol of triethylenediamine was added and stirred until dissolved. The mixture was placed in a 100 mL stainless steel autoclave and hydrothermally treated at 120 °C for 48 h. After cooling to room temperature, the precipitate was collected by centrifugation (10000 rpm, 5 min), and washed with anhydrous methanol and DMF 3 times. The washed precipitate was then vacuum dried at 60 °C for 12 h to obtain N-doped MOFs material (abbreviated as Co-MOFs@N material).

[0069] 0.1 g of Co-MOF@N material was ultrasonically dispersed in 80 mL of ethanol solution to prepare Co-MOF@N ethanol dispersion, and 0.1 mol / L NaOH alkaline solution was used to adjust the pH of the dispersion to 8, then 50 mg of porogen hexadecyltrimethylammonium bromide (CTAB) was added, and the mixture was stirred and mixed evenly. Then, a mixed solution containing 10 mL of tetraethyl orthosilicate and 60 mL of ethanol was slowly added dropwise to the above mixture, and the mixture was stirred and reacted at room temperature for 20 h. The reaction solution was filtered to obtain a solid, and then the separated solid was placed in an ethanol solution and heated to reflux to remove the residual CTAB in the pores. After the reflux, it was filtered again, and the obtained solid was dried at 60 ° C for 12 h to obtain a N-doped modified MOFs precursor with SiO2 coated on the surface (referred to as Co-MOF@N@SiO2 precursor).

[0070] 2) Preparation of Co3O4@NC@SiO2 by two-step calcination method The Co-MOF@N@SiO2 precursor prepared in step (1) was calcined for the first time under a nitrogen protective atmosphere at a calcination temperature of 300 °C, a heating rate of 3 °C / min, and a time of 2 h; then it was calcined for the second time under an air atmosphere at a calcination temperature of 400 °C, a heating rate of 3 °C / min, and a time of 3 h. After cooling to room temperature, a black solid powder was obtained, namely, an N-doped modified MOFs-derived core-shell nanoreactor (abbreviated as Co3O4@NC@SiO2).

[0071] Figure 2 This is the SEM image of Co3O4@NC@SiO2. It can be seen that the Co3O4@NC@SiO2 catalyst prepared in this example has a core-shell structure, and SiO2 serves as a shell layer to coat Co3O4@NC.

[0072] Comparative Example 1 A cobalt salt solution and an organic ligand solution were prepared according to the method provided in Example 1, and then the organic ligand solution was added to the cobalt salt solution, and hydrothermally treated at 120 ° C for 48 h in a 100 mL stainless steel high-pressure reactor. After cooling to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed three times with anhydrous methanol and DMF, and then the washed precipitate was vacuum dried at 60 ° C for 12 h to obtain a Co-MOF material.

[0073] The Co-MOF material prepared in step (1) was calcined according to the method provided in Example 1 to obtain Co3O4@C.

[0074] Comparative Example 2 The Co-MOF@N material was prepared according to the method provided in Example 1, and the Co-MOF@N material was calcined to obtain Co3O4@NC.

[0075] Comparative Example 3 1) Preparation of Co-MOF@SiO2 materials by solvothermal method A cobalt salt solution and an organic ligand solution were prepared according to the method provided in Example 1, and then the organic ligand solution was added to the cobalt salt solution, and hydrothermally treated at 120 ° C for 48 h in a 100 mL stainless steel high-pressure reactor. After cooling to room temperature, the precipitate was collected by centrifugation, and the precipitate was washed three times with anhydrous methanol and DMF, and then the washed precipitate was vacuum dried at 60 ° C for 12 h to obtain a Co-MOF material.

[0076] 0.1 g of Co-MOF material was ultrasonically dispersed in 80 mL of ethanol solution to prepare Co-MOF ethanol dispersion, and the pH of the dispersion was adjusted to 8 using 0.1 mol / L NaOH alkaline solution, and then 50 mg of porogen hexadecyltrimethylammonium bromide (CTAB) was added and stirred to mix evenly. A mixed solution containing 10 mL of ethyl orthosilicate and 60 mL of ethanol was slowly added dropwise to the above mixed solution, and the reaction was stirred at room temperature for 20 h. The reaction solution was filtered to obtain a solid, and then the separated solid was placed in an ethanol solution and heated to reflux to remove the residual CTAB in the pores. After the reflux, it was filtered again, and the obtained solid was dried at 60 ° C for 12 h to obtain the Co-MOF@SiO2 precursor.

[0077] 2) Preparation of Co3O4@C@SiO2 by two-step calcination method The Co-MOF@SiO2 precursor prepared in step (1) was calcined according to the method provided in Example 1 to obtain Co3O4@C@SiO2.

[0078] Example 2 0.1 g of the catalyst prepared above, 2 g of furfural, and 10 g of isopropanol were added to a magnetic stirring high-pressure mechanical reactor with a 25 mL liner. After the reactor was sealed, the air in the reactor was replaced 3 times, and then the inlet valve was opened to introduce 0.5 MPa of nitrogen, and heating began. When the temperature in the reactor reached the reaction temperature of 100 °C, the main valve and the air inlet valve of the nitrogen bottle were opened. When the pressure in the reactor increased to the reaction pressure of 1.0 MPa, the reaction start time was recorded. The reaction ended after 12 h, and the main valve of the nitrogen bottle and the air inlet valve of the reactor were closed. Then the reactor was placed in a cold water bath and cooled to room temperature. The cooled reaction solution was taken out, the catalyst was removed by centrifugation, and the amount of the reaction product was determined by gas chromatography. The results are shown in Table 1.

[0079] Table 1 Catalytic performance of different materials for transfer hydrogenation of furfural to furfuryl alcohol

[0080] As can be seen from Table 1, compared with other materials, the N-doped modified MOFs-derived core-shell nanoreactor (Co3O4@NC@SiO2) prepared in the embodiment of the present application can significantly improve the conversion rate of furfural, with a conversion rate of more than 99%, and can even achieve complete conversion of furfural, while the selectivity of furfuryl alcohol is high. The Co3O4@NC@SiO2 prepared in the present application can achieve high conversion and high selectivity to prepare furfuryl alcohol under mild conditions (reaction temperature of 100 °C and reaction pressure of 1.0 MPa).

[0081] Example 3 In Example 2, Co3O4@NC@SiO2 has the best effect in catalyzing the transfer hydrogenation of furfural to prepare furfuryl alcohol, followed by Co3O4@NC. Therefore, the reaction solution containing Co3O4@NC@SiO2 and Co3O4@NC in Example 2 was centrifuged, the precipitate was collected and washed with ethanol and centrifuged 3 times, vacuum dried at 80°C for 12 h, the catalyst was recovered, and then the recovered material was used to catalyze the transfer hydrogenation reaction of furfural according to the method provided in Example 2. After the reaction was completed, the reaction product and the catalyst were collected by centrifugation, and the amount of the reaction product was determined by gas chromatography. The precipitate collected by centrifugation was washed with ethanol and centrifuged 3 times, vacuum dried at 80°C for 12 h, and then used again to catalyze the transfer hydrogenation reaction of furfural to achieve recycling. The reaction results of furfural transfer hydrogenation to prepare furfuryl alcohol corresponding to the number of material recycling times are shown in Tables 2 and 3.

[0082] Table 2 Reaction results corresponding to the number of cycles of Co3O4@NC@SiO2

[0083] Table 3 Reaction results corresponding to the number of Co3O4@NC cycles

[0084] It can be seen from Tables 2 and 3 that the furfural conversion rate corresponding to Co3O4@NC decreases significantly with the increase in the number of cycles. The reason may be that Co3O4@NC is not coated with SiO2 as a shell layer, and the material structure is unstable, resulting in a decrease in the catalytic effect during the cycle. The Co3O4@NC@SiO2 prepared in this application has a core-shell structure. During the material preparation and catalytic reaction process, the skeleton structure is stable and will not collapse, thereby affecting the catalytic effect. Specifically, after the Co3O4@NC@SiO2 prepared in this application was recycled 4 times, the corresponding furfural conversion rate was still greater than 98%, and the furfuryl alcohol selectivity was still greater than 94%. It can still achieve high conversion and high selectivity to prepare furfuryl alcohol under mild conditions (reaction temperature of 100 ° C, reaction pressure of 1.0 MPa), which shows that Co3O4@NC@SiO2 has excellent cycle stability and can be reused.

[0085] Example 4 A certain amount of cobalt salt Co(NO3)2·6H2O and a certain amount of organic ligand terephthalic acid were dissolved in 45 mL of N,N-dimethylformamide solvent, and ultrasonically dispersed to obtain a cobalt salt solution and an organic ligand solution. The organic ligand solution was added to the cobalt salt solution, and then a certain amount of nitrogen source triethylenediamine was added and stirred to dissolve. The mixture was placed in a 100 mL stainless steel autoclave and hydrothermally treated at 120 °C for 48 h. After cooling to room temperature, the precipitate was collected by centrifugation and washed with anhydrous methanol and DMF for 3 times. The washed precipitate was then vacuum dried at 60 °C for 12 h to obtain Co-MOF@N material, wherein the molar amounts of cobalt source, terephthalic acid and nitrogen source are shown in Table 4. The above Co-MOF@N material was prepared into a Co-MOF@N@SiO2 precursor according to the method provided in Example 1, and calcined to obtain Co3O4@NC@SiO2.

[0086] The performance of the Co3O4@NC@SiO2 prepared above in catalyzing the transfer hydrogenation of furfural to prepare furfuryl alcohol was tested according to the method provided in Example 2. The results are shown in Table 4.

[0087] Table 4 Reaction results corresponding to the millimolar dosage of cobalt salt, organic ligand and nitrogen source

[0088] It can be seen from Table 4 that by adjusting the molar ratio of cobalt salt, organic ligand and nitrogen source, the content of Co and N in the N-doped modified MOFs material can be regulated, and the pore structure, specific surface area, morphology and stability of the material can be controlled, thereby improving the catalytic activity of the material.

[0089] Example 5 According to the method provided in Example 1, a Co-MOF@N material was prepared, and then a certain amount of Co-MOF@N material was ultrasonically dispersed in 80 mL of ethanol solution to prepare a Co-MOF@N ethanol dispersion, and a 0.1 mol / L NaOH solution was used to adjust the pH of the dispersion to 8, and then a certain amount of porogen hexadecyltrimethylammonium bromide (CTAB) was added, and the mixture was stirred and mixed evenly, and then a mixed solution containing different volumes of tetraethyl orthosilicate (TEOS) and 60 mL of ethanol was slowly added dropwise to the above dispersion, and stirred at room temperature for reaction. The reaction solution was filtered to obtain a solid, and then the separated solid was placed in an ethanol solution and heated to reflux to remove the residual CTAB in the pores. After the reflux, it was filtered again, and the obtained solid was dried to obtain a Co-MOF@N@SiO2 material, wherein the amount of Co-MOF@N material, porogen and tetraethyl orthosilicate is shown in Table 5. According to the method provided in Example 1, the above MOF@N@SiO2 precursor was calcined to obtain Co3O4@NC@SiO2.

[0090] The performance of the Co3O4@NC@SiO2 prepared above in catalyzing the transfer hydrogenation of furfural to prepare furfuryl alcohol was tested according to the method provided in Example 2. The results are shown in Table 5.

[0091] Table 5 Reaction results corresponding to the dosage of Co-MOF@N, porogen and TETS

[0092] It can be seen from Table 5 that by adjusting the dosage of Co-MOF@N, porogen and tetraethyl orthosilicate, the pore structure of the material can be precisely controlled and the adsorption capacity and catalytic activity of the material can be optimized. Tetraethyl orthosilicate can be hydrolyzed to form silica coated with MOFs to obtain a material with a core-shell structure, which can provide additional pore space, increase the specific surface area of ​​the material, and improve the chemical and thermal stability of the material.

[0093] Example 6 The MOF@N@SiO2 precursor was prepared according to the method provided in Example 1, and then the Co-MOF@N@SiO2 precursor was calcined for the first time under a nitrogen protective atmosphere, and then calcined for the second time under an air atmosphere. The specific calcination parameters are shown in Table 6. After cooling to room temperature, a black solid powder, namely Co3O4@NC@SiO2, was obtained.

[0094] The performance of the Co3O4@NC@SiO2 prepared above in catalyzing the transfer hydrogenation of furfural to prepare furfuryl alcohol was tested according to the method provided in Example 2. The results are shown in Table 6.

[0095] Table 6 Reaction results corresponding to calcination parameters

[0096] As can be seen from Table 6, the present application uses a two-step pyrolysis method to perform the first calcination of the above-mentioned N-doped modified MOFs precursor with SiO2 coated on the surface under an inert atmosphere, which can retain the porous structure of MOFs, avoid the complete destruction of the material structure at high temperature, and form a material with high specific surface area and porosity and stable pore structure. Then, the second calcination is performed in an oxygen-containing atmosphere, which can further optimize the material structure, promote the complete oxidation of organic ligands, and form the required metal oxide phase (i.e., cobalt oxide phase), and further regulate the pore structure and surface properties of the material, improve the catalytic activity and stability of the material, and obtain an N-doped modified MOFs-derived core-shell nanoreactor.

[0097] Example 7 0.1 g of Co3O4@NC@SiO2 prepared in Example 1, 2 g of different types of α, β-unsaturated aldehydes (such as furfural, 5-hydroxymethylfurfural, acrolein, 2-furan acrolein, cinnamaldehyde, 4-methylcinnamaldehyde, 4-fluorocinnamaldehyde, 4-bromocinnamaldehyde), and 10 g of isopropanol were added to a magnetic stirring high-pressure mechanical reactor with a 25 mL liner. After the reactor was sealed, the air in the reactor was replaced 3 times with nitrogen, and then the inlet valve was opened to introduce 0.5 MPa of nitrogen, and heating began. When the temperature in the reactor reached the reaction temperature of 100 °C, the main valve and the air inlet valve of the nitrogen bottle were opened. When the pressure in the reactor increased to the reaction pressure of 1.0 MPa, the reaction start time was recorded. The reaction was completed after 12 h, and the main valve of the nitrogen bottle and the air inlet valve of the reactor were closed. Then, the reactor was placed in a cold water bath and cooled to room temperature. The cooled reaction solution was taken out, the catalyst was removed by centrifugation, and the amount of the reaction product was determined by gas chromatography. The results are shown in Table 7.

[0098] Table 7 Catalytic performance of Co3O4@NC@SiO2 in transfer hydrogenation of α,β-unsaturated aldehydes

[0099] It can be seen from Table 7 that the Co3O4@NC@SiO2 prepared in the examples of the present application has a high conversion rate for different types of α, β-unsaturated aldehydes, while improving the selectivity of α, β-unsaturated alcohols, and has excellent catalytic performance.

[0100] Embodiments 8 to 12 Cobalt chloride and cobalt acetate were used to replace cobalt nitrate hexahydrate as cobalt salt, and the other conditions were the same as in Example 1 to prepare Co3O4@NC@SiO2-1 and Co3O4@NC@SiO2-2. Urea, melamine and polyaniline were used to replace triethylenediamine as nitrogen source, and the other conditions were the same as in Example 1 to prepare Co3O4@NC@SiO2-3, Co3O4@NC@SiO2-4 and Co3O4@NC@SiO2-5.

[0101] The performance of the materials prepared in Examples 8 to 12 in catalyzing the transfer hydrogenation of furfural to prepare furfuryl alcohol was tested according to the method provided in Example 2.

[0102] The experimental results show that the furfural conversion rates corresponding to the materials prepared in Examples 8 to 12 are all greater than 99%, and the furfural selectivity is greater than 94%. Furfuryl alcohol can be prepared with high conversion rate and high selectivity under mild conditions (reaction temperature of 100 °C and reaction pressure of 1.0 MPa).

[0103] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for preparing an N-doped modified MOFs-derived core-shell nanoreactor, characterized in that: The steps include: S1, mixing a cobalt salt, an organic ligand, a nitrogen source and a first solvent for hydrothermal treatment, then collecting a precipitate by centrifugation, and obtaining a N-doped modified MOFs material after washing and drying; S2, dispersing the N-doped modified MOFs material in a second solvent to obtain a dispersion, then adjusting the pH of the dispersion, adding a porogen and ethyl orthosilicate, stirring to react, filtering and collecting the solid, washing, and drying to obtain an N-doped modified MOFs precursor with SiO2 coated on the surface; S3. The N-doped modified MOFs precursor with SiO2 coated on the surface is subjected to a first calcination under an inert atmosphere to form a porous structure; and then subjected to a second calcination under an oxygen-containing atmosphere to promote the complete oxidation of the organic ligand and the formation of a cobalt oxide phase, thereby obtaining an N-doped modified MOFs-derived core-shell nanoreactor.

2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of the cobalt salt, the organic ligand and the nitrogen source is (3-5):(3-6):(2-5).

3. The preparation method according to claim 1, characterized in that: The cobalt salt is one or more of cobalt chloride, cobalt acetate, cobalt nitrate and cobalt nitrate hydrate; and / or, The nitrogen source is one or more of triethylenediamine, urea, melamine and polyaniline; and / or, The organic ligand is terephthalic acid; and / or, The first solvent and the second solvent are each independently methanol, ethanol, N,N -dimethylformamide, N,N - one or more of diethylformamide and dimethyl sulfoxide.

4. The preparation method according to claim 1, characterized in that In step S1, the temperature of the hydrothermal treatment is 100°C to 150°C, and the time of the hydrothermal treatment is 24 h to 72 h; and / or, The drying temperature is 50°C to 80°C, and the drying time is 10 h to 15 h.

5. The preparation method according to claim 1, characterized in that: In step S2, an acid-base regulator is used to adjust the pH of the dispersion to 8-9, and the acid-base regulator is one or more of sodium hydroxide, potassium hydroxide and ammonia water.

6. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the N-doped modified MOFs material to the porogen is 1:(0.1-1); the concentration of the tetraethyl orthosilicate in the dispersion is 5%-10%; Optionally, the porogen is one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide.

7. The preparation method according to claim 1, characterized in that: In step S3, the inert atmosphere includes one or more of nitrogen, argon, neon, helium, xenon and krypton; and / or, The oxygen-containing atmosphere comprises oxygen and / or air; and / or, The first calcination is carried out at a temperature of 300°C to 350°C, for a time of 2 h to 4 h, at a heating rate of 2°C / min to 5°C / min; and / or, The second calcination is carried out at a temperature of 350°C to 450°C, for a time of 2 h to 4 h, and at a heating rate of 2°C / min to 5°C / min.

8. An N-doped modified MOFs-derived core-shell nanoreactor, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. Use of the N-doped modified MOFs-derived core-shell nanoreactor as claimed in claim 8 in catalyzing the transfer hydrogenation reaction of α,β-unsaturated aldehydes.

10. The use according to claim 9, characterized in that: The α,β-unsaturated aldehydes include one or more of furfural, 5-hydroxymethylfurfural, acrolein, 2-furanacrolein, cinnamaldehyde, 4-methylcinnamaldehyde, 4-fluorocinnamaldehyde, 4-bromocinnamaldehyde, crotonaldehyde and citral; and / or, The mass ratio of the N-doped modified MOFs-derived core-shell nanoreactor and the α,β-unsaturated aldehyde is (0.025-0.05):(0.8-1).

Citation Information

Cited By

  • Method for preparing furfuryl alcohol through selective hydrogenation of furfural

    CN120172935A

  • MOF-derived hollow mesoporous LaFeO3 / La2O3-based triethylamine gas sensor

    CN120651921A

  • A hollow mesoporous LaFeO3 / La2O3-based triethylamine gas sensor based on MOF derivation

    CN120651921B